The Appointment of New Hamas Leader in Al Jazeera Arabic 2024 : A Critical Discourse Analysis - Zulfan; Mahmud Khudri; Muhammad, Habibullah Al Magribi; Nursukma Suri; Windi Chaldun (Islam Transformatif : Journal of Islamic Studies, 2025)
This research is designed to demonstrate (1) how critical discourse analysis in Al Jazeera Arabic media about the appointment of Yahya Sinwar as the new leader of Hamas (specifically on August 7-9, 2024) and (2) how Al Jazeera Arabic constructs discourse with indications of favoritism to one of the parties between Palestine and Israel. To collect and analyze the research data, researchers used descriptive qualitative methodology as a scientific research procedure. The collected data is classified into three data, namely primary data, secondary data, and supporting data. Furthermore, in analyzing the data, researchers applied Teun A. Van Dijk's critical discourse analysis (CDA) as a linguistic theory to understand and study the discourse in the news of Yahya Sinwar's appointment in Al Jazeera Arabic media. The results showed (1) the existence of a microstructure of semantic points that includes aspects of setting, details, intent, and presupposition and (2) the news writer has a clear tendency to favor Hamas, as reflected in the choice of words and sentence construction used in the news. Keyword : Critical Discourse Analysis Theory1, Teun A. Van Dijk2, New Leader3, Hamas4, Al Jazeera Arabic5.